A Research On The Relationship Between Organizational Silence And Burnout - Coban, Hatice; Sarikaya, Mehtap (European Scientific Journal, ESJ, 2016)
Organizational silence and burnout are two of the most important organizational issues and both of them create obstacles for the development and survival of organizations. Organizational silence as opposite to organizational voice, is expressed as the state of employees being unable to declare their ideas on organizational matters freely. Dimensions of organizational silence examined with these three forms: acquiescent silence, defensive silence and prosocial silence. Burnout as a kind of job stress, is a syndrome caused by working interactively with other people. Dimensions of burnout examined as emotional exhaustion, depersonalization and reduced personal accomplishment. In the first part of this study, literature review on organizational silence and burnout has been summarized. And then, in the second part, a quantitative research has been conducted on the administrative staff of a state university in Turkey to determine the relationship between organizational silence and burnout and to test the research model. According to the research results, some of the hypotheses were approved and some of them were rejected. Thus, the research model was partly supported.